Effect of the COVID‐19 Pandemic on Otolaryngology Trainee Surgical Case Numbers: A Multi‐institutional Review. (28th December 2022) - Mann, Scott; Duffy, James; Muffly, Tyler; Tilva, Keval; Gray, Stacey; Hetzler, Laura; Kraft, Shannon; Malekzadeh, Sonya; Pletcher, Steven; Cabrera-Muffly, Cristina
Abstract: Objective: To determine the effect of the initiation of COVID‐19–related restrictions on the volume of surgical cases performed by otolaryngology trainees. Study Design: Multi‐institutional retrospective analysis of resident surgical case logs. Setting: Accredited residency training programs in otolaryngology head and neck surgery. Methods: Resident surgical case logs were combined from 6 residency training programs from different regions of the United States. Case volumes were compared between the calendar year before March 1, 2020, and the year afterward. Subgroup analyses were performed for the type of hospital (university, pediatric, veteran, county) and the key index cases by subspecialty. Results: All 6 participating residency programs had a decrease in resident operative case volume. Surgical volume decreased from a mean of 6014 to 4161 ( P < .05). There were decreases observed in key index cases in every subspecialty ( P < .01), without statistical differences seen among subspecialties. There were decreases observed in every hospital type (university, pediatric, veteran, county) without statistical differences among types. Postgraduate year 5 residents were the most affected by volume reductions (51.6%), and postgraduate year 3 residents were the least affected (1.4%). Conclusion: In the year following initiation of COVID‐19–related restrictions, there was a significant decrease in trainee surgical case volumes within residencies for otolaryngology–head and neck surgery. There were no statistical differences in the volume decreases seen at different institutions, among hospital types, or within various subspecialties.